IMPLEMENTATION THE WAREHOUSE RECEIPT SYSTEM AS ONE OF BANKING CREDIT GUARANTEE ACCORDING TO ACT ON WAREHOUSE RECEIPT SYSTEM - Lathifah Hanim (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
Warehouse receipt system is the most secure and sophisticated when compared to some systems that ever existed in Indonesia. In the warehouse receipt system, there is a guarantee of security for banks, because all the data administration of the warehouse receipt concentrated in the Registration Center and overseen by the Supervisory Board (BAPPEBTI) and there is no assurance of quality for the goods owners and prospective owners of the goods because the goods stored properly managed by the manager of the warehouse and quality tested previously by an independent conformity assessment body that has been certified from KAN approved by BAPPEBTI. The method used is doctrinal and non-doctrinal. Research results are 1). Implementation of Warehouse Receipt System as One Credit Guarantee as PP No.36 Of 2007 Article 34 (2), 35 (2), 25 (1) stated that every person who manipulates the data / information related to warehouse receipt and warehouse receipt derivatives defined in Article 35 shall be sentenced to imprisonment for a maximum of 8 (eight) and a maximum fine of Rp.10.000.000.000, - (ten billion rupiah). 2). Obstacles and solutions in the implementation of the Warehouse Receipt System, including transaction costs, inconsistencies in the quantity and quality of agricultural products, the lack of institutional support agriculture, and the still weak institutional farmers. So, this article would like to discuss intensively